1997 - Goh, Wei Choon (2014)
Our project is a 7-8 minute animated mood piece exploring what it was like to be a kid in Singapore in the 90's. The film would follow 2 protagonists, a boy and a girl, as they deal with their seemingly outcast and lonely school lives by embarking on highly imaginative flights of fantasy and fancies. It is essentially a social documentation through 2 unreliable but keen observers on Singapore in the 90's.